Effect of maleic hydrazide on induction of seed dormancy and seed quality parameters in rice - SOOGANNA; L.V. SUBBARAO; P. KIRAN BABU; U. CHAITANYA; K. KESHAVULU (Seed Research, 2026)
Seed dormancy in rice is controlled by its genetic and environmental factors. It is necessary to prevent pre harvest sprouting which is more common. To induce seed dormancy a field experiment was conducted by using maleic hydrazide (MH) as a foliar spray with two different concentrations at the time of flowering in twenty non dormant rice cultivars. The induction of dormancy was tested by conducting germination test immediately after harvest up to the stage where the germination had reached to Indian minimum seed certification standard (80%). The dormancy duration was computed as the period from harvest till the germination reached to 80% in each entry. The germination percentage was recorded every 15 days, starting from 5 DFH (Days from harvesting) up to 35 DFH. The germination percentage was more in control (T₁) and lower values were observed in seeds treated with MH @ 20000 ppm followed by MH @ 10000 ppm. The shoot length, root length and seedling vigour index were found more in control and lower values were observed in MH @ 20000 ppm followed by MH @ 10000 ppm. It is concluded that, the foliar spray of MH @ 20000 ppm could induce seed dormancy that persisted from 30 to 35 days in 17 varieties with exceptions being RP Bio 226, Mahsuri and DRR Dhan 38.